In the shadow of a people's president - Cooray, Evans (Colombo : Vijitha Yapa Publications, 2008)
On life and times of former Sri Lankan president R. Premadasa, 1924-1993; autobiographical account of Evans Cooray, former press secretary to the Sri Lankan president.
Keywords: Premadasa, R., -- 1924-; Cooray, Evans; Presidents -- Sri Lanka -- Biography; Politicians -- Sri Lanka -- Biography; Sri Lanka -- Politics and government -- 1978-